Strategi Pengembangan Bisnis Abon Di Umkm Langkah Maju - saputra, Yehuda Nathanael Theo; Pengestu, Seto Probo; Prabawati, Malicha; Wahyudi, Alfarobi Sabilar Rosyad; Pratama, Chabib Galuh; Saputra, Adithya (Journal of Agribusiness, Social and Economic, 2025)
This study aims to analyze the business development strategy of abon (shredded meat) at UMKM Langkah Maju using a SWOT approach. The analysis evaluates internal factors, including strengths and weaknesses, as well as external factors, such as opportunities and threats that affect business growth. The results indicate that UMKM Langkah Maju's main strengths lie in high-quality raw materials, distinctive flavors, and competitive pricing. However, challenges such as limited production capacity, suboptimal marketing, and competition with large-scale abon producers remain significant. By leveraging opportunities such as increasing market demand, digital marketing, and government support, the recommended strategies include market expansion, product innovation, and branding improvement. This study is expected to serve as a reference for developing creative economy-based MSMEs to enhance competitiveness and achieve sustainable business growth.